News Headline Strategy and Selection by the Editorial Teams of Sumut Pos and Tribun Medan Newspapers in Maintaining Circulation During the Digital Disruption Era - Sisworo, Ari; Rudianto, Rudianto; Thariq, Muhammad (Persepsi: Communication Journal, 2024)
Digital disruption is a popular phrase today and makes print media must really strategise, especially in determining news headlines as the main presentation. This study aims to analyse the strategy of the North Sumatra Pos and Tribun Medan Daily Editors in determining news issues that will be used as headlines, so that they can attract readers' interest. The objects in this study are Sumut Pos and Tribun Medan newspapers whose news is presented in printed form. Researchers took three news in each media from the May-June 2024 time span. This time span was chosen, to show the selection process of news titles published with the number of copies of each edition. The theory used is the concept of gatekeeping from David Mannining White (1950), which generally describes the selection process in the work of the media, especially the decision whether a news story can pass through the ‘gate’ to be aired on the news channel. The method used is descriptive qualitative with an interpretative approach, and a comparative study technique. The results showed that both media conducted the same process, starting from planning at the projection meeting, determined through a budget meeting, and the news agreed upon by the gatekeepersis news that is considered worthy of going up and becoming a headline by prioritising the news value contained in it. News or issues that develop in online media and social media or new media are also a reference for both media, but with a more in-depth presentation and different perspectives.